A current-mode stimulator circuit with two-step charge balancing background calibration - Xiong, Gordon M. (2013)
Current-mode CMOS stimulation systems have offered unprecedented opportunities for accurate and high through put in-vitro and in-vivo physiological studies. As these circuits are in long term contact with living organisms, they must be flexible, safe and power efficient. Any mismatch in biphasic current pulses will result in charge imbalance, leading to tissue/cell damage. Therefore, it is the most important to maintain the balance of the charge injected and retracted by the anode and the cathode, respectively. This work first adjusts the body biasing voltage of the anode to match with the cathode current. It is robust, process-variation-aware and can reduce the imbalanced current to less than 1%. Second, any residue charge at the stimulation site is retracted only when it reaches a critical value. This process is performed in the background and thus does not disturb the front-end operation. Overall, it can achieve less than 0.4 nA DC error current and thus is a suitable candidate for long term stimulation applications.